2011
DOI: 10.1007/978-1-4419-9716-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Modal Analysis of CX-100 Rotor Blade and Micon 65/13 Wind Turbine

Abstract: This accounts for 1.25% of all U.S. electricity generated and enough to power 7 million homes. As wind energy becomes a key player in power generation and in the economy, so does the performance and reliability of wind turbines. To improve both performance and reliability, smart rotor blades are being developed that collocate reference measurements, aerodynamic actuation, and control on the rotor blade. Towards the development of a smart blade, SNL has fabricated a sensored rotor blade with embedded distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…General reviews can be found in [9] and [10]. Several researchers have tried in recent years to apply damage detection technologies, and these studies were mainly in a laboratory environment [11]- [18]. Briefly, both passive and active sensing technologies have been applied in the context of WTs [13].…”
Section: Introductionmentioning
confidence: 99%
“…General reviews can be found in [9] and [10]. Several researchers have tried in recent years to apply damage detection technologies, and these studies were mainly in a laboratory environment [11]- [18]. Briefly, both passive and active sensing technologies have been applied in the context of WTs [13].…”
Section: Introductionmentioning
confidence: 99%
“…The first two scenarios were chosen to verify that the issues that arose from a previous code verification study [13] were resolved with the new ANSYS Shell281 elements. The verification of the modal analysis was also demonstrated because a modal analysis is one of the most typical dynamic characterizations ( [18], [19], and [20]). …”
Section: Code Verification With Ansysmentioning
confidence: 99%
“…This particular blade has been widely studied [35,36,37]. A simplified finite element model was generated in ANSYS using shell elements.…”
Section: Wind Turbine Blade Modelmentioning
confidence: 99%